LANGUAGE NEEDS ANALYSIS OF STUDENTS AT PHYSICS EDUCATION DEPARTMENT FACULTY OF TEACHER TRAINING AND EDUCATION, MATARAM UNIVERSITY - Afrizal Rizki Samudra; I Made Sujana; Ahmad Zamzam (Program Studi Pendidikan Bahasa Inggris, 2021)
The purposes of this study are to: (1) describe the students’ level of English at Physics Education Department, University of Mataram; (2) describe the needs of English perceived by the students at Physics Education Department; and (3) describe the needs of English perceived by English lecturers at Physics Education Department. It employed a mixed method by combining both quantitative and qualitative research. The subject of this research was 55 students at the Physics Department and 3 English lecturers. The data were collected by using a triangulation technique such as test (placement test), questionnaire, and interview. The result of the test showed that (1) most of the students’ level of English are in the elementary level; (2) students and English teachers perceived the language needs differently. These situations caused conflicts in designing language programs between the results of Present Situation Analysis (PSA), and Target Situation Analysis (TSA).